2015
DOI: 10.1111/cbdd.12652
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Fluorinated 3‐Phenylcoumarin‐7‐O‐Sulfamate Derivatives as Steroid Sulfatase Inhibitors

Abstract: In the present work, we report the initial results of our study on a series of 3-phenylcoumarin sulfamate-based compounds containing C-F bonds as novel inhibitors of steroid sulfatase. The new compounds are potent steroid sulfatase inhibitors, possessing more than 10 times higher inhibitory potency than coumarin-7-O-sulfamate. In the course of our investigation, compounds 2b and 2c demonstrated the highest inhibitory effect on the enzymatic steroid sulfatase assay; both had IC50 values of 0.27 μm (the IC50 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…[5] Various approaches have been used in the design of effective STS inhibitors. [11] In most cases, compounds containing C-F bonds showed slightly higher STS inhibitory activity than the corresponding analogs without the fluorine atom. [6] One of the most promising compounds was steroidal EMATE (Figure 1), which exhibited a very high activity in MCF-7 cells, with an IC 50 value of 65 pm.…”
Section: Introductionmentioning
confidence: 97%
“…[5] Various approaches have been used in the design of effective STS inhibitors. [11] In most cases, compounds containing C-F bonds showed slightly higher STS inhibitory activity than the corresponding analogs without the fluorine atom. [6] One of the most promising compounds was steroidal EMATE (Figure 1), which exhibited a very high activity in MCF-7 cells, with an IC 50 value of 65 pm.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, extensive research on the preparation of many coumarin derivatives as STS inhibitors has been carried out. Inhibitory activity against STS was determined in the case of phosphate and thiophosphate derivatives of tricyclic coumarin (Kozak et al, ; Kozak et al, ), fluorinated derivatives of 3‐phenylcoumarin‐7‐ O ‐sulfamate (Demkowicz et al, ) and fluorinated N ‐benzoyl and N ‐phenylacetoyl derivatives of 3‐(4‐aminophenyl)‐coumarin‐7‐ O ‐sulfamate (Daśko et al, ). For example, compounds 4 and 5 demonstrated inhibitory activity with an IC 50 value of 180 nM (for both compounds) in an assay with isolated STS.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Further development of this series of nonsteroidal inhibitors led to the discovery of the tricyclic coumarin sulfamate ( 2 ) (Irosustat, STX64, 667COUMATE, BN83495, Figure 1 ) which has proven to be the most successful STS inhibitor to date. 12 , 16 Recently, other examples of both mono- 20 , 21 and two-ring sulfamate-based STS inhibitors 22 have been published, but these compounds are generally still of relatively modest inhibitory activity. Irosustat was the first STS inhibitor to enter clinical trials for postmenopausal patients with advanced HDBC and has shown encouraging results.…”
Section: Introductionmentioning
confidence: 99%